Safety of tooth extraction in patients receiving direct oral anticoagulant treatment versus warfarin: a prospective observation study. Issue 8 (August 2019) - Yoshikawa, H.; Yoshida, M.; Yasaka, M.; Yoshida, H.; Murasato, Y.; Fukunaga, D.; Shintani, A.; Okada, Y.
Abstract: The aim of this study was to compare the safety of tooth extraction in patients receiving direct oral anticoagulants (DOACs) or warfarin without cessation of their antithrombotic treatment. This prospective observational study included 367 patients undergoing tooth extraction (119 receiving DOACs and 248 receiving warfarin). All extractions in DOAC patients were performed 6–7 h after taking DOACs in consideration of the half-life in blood under continued antithrombotic treatment. To examine the potential postoperative bleeding risk related to the time of extraction and the drug concentration of blood, activated partial thromboplastin time (APTT) in dabigatran and prothrombin time (PT) in rivaroxaban were measured three times after administration. A total of 390 tooth extractions were performed: 128 in the DOAC patients and 262 in warfarin patients. Postoperative bleeding occurred in four extractions (3.1%) in the DOAC group and in 23 (8.8%) in the warfarin group. There was no statistically significant difference between the two groups (odds ratio: 2.362, 95% confidence interval (CI) 0.819–6.815, p  = 0.112). APTT and PT prolongation in almost all cases decreased with time after taking the medicine. Our findings suggest that interruption of DOAC therapy is not necessary for tooth extraction if the procedure is performed at least 6 h after the last dose.